Polar patrol balloon II. Observation Plan - Masahiro Kodama; Hiroshi Fukunishi (National Institute of Polar Research, 1984)
As described in Part I, from a feasibility study of the Polar Patrol Balloon (PPB) which circles along a selected geographic latitude over Antarctica, it has been concluded that the PPB will be developed in the near future. The application of the PPB system is discussed in this paper. By the PPB experiment many subjects of upper atmosphere physics, meteorology, glaciology, cosmic ray physics and logistics will be solved, the subjects which have not been solved by technique of spacecraft and sounding rocket.